Contributions and difficulties of the nursing team in the implementation of palliative care for cancer patients (Research, Society and Development, 2021)
Cancer is an overwhelming disease and palliative care must be present from the moment the disease becomes aggressive and at an advanced stage, and it is an assignment of the nursing team to plan and offer it to patients. The objective was to analyze the contributions and difficulties of nursing in the implementation of palliative care to terminal cancer patients. The search for articles was performed in the databases indexed in the Virtual Health Library, between July and November 2020, using the Prisma methodology. The sample included 14 articles that addressed the theme, 92.8% in the English language and only 7.1% national. In addition, 35.7% are productions from European countries and 28.5% are from North America. The largest number of publications in European countries may be related to the fact that Europe is the birthplace of the study on palliative care. The studies included the importance of oncology nursing in the provision of end-of-life care. However, these professionals have difficulty dealing with the physical and emotional pain stems from patients, fears about anticipating palliative care planning, lack of confidence in communicating with the patient in times of concern, fears and longings regarding the death and dying process, emotional attachment, doubts of what are their real duties in care and limitations such as lack of time to perform face-to-face or online training/training.